A narrative review of interventions for post-stroke frailty: current advances and future directions - Fan, Xiaowen; Xia, Yi; Xu, Shengwang; Jia, Shulei (Frontiers in Neurology, 2025)
Frailty affects the health outcomes of stroke patients. Timely identification of the progression of frailty in stroke patients and intervention play a crucial role in prognosis. This article reviews domestic and international literature on frailty interventions for stroke patients, focusing on the definition of stroke combined with frailty, frailty staging, and the effects of exercise, nutritional, cognitive, and psychosocial interventions, and medication management on the prognosis of stroke. The aim is to provide a reference for improving the prognosis of stroke patients with frailty.